Mengatasi Ketimpangan: Pembelajaran dari Praktik Global untuk Pendidikan di Wilayah Terpencil Indonesia - sugihyono sugihyono (Journal on Education, 2025)
Education in remote areas of Indonesia faces significant challenges that hinder access to and the quality of learning. Economic factors, geographical limitations, ineffective school management, low teacher competency, and inadequate infrastructure and external support are the main obstacles to creating an inclusive and sustainable education system. This study aims to analyze the key challenges in rural education in Indonesia and explore policy-based solutions by referencing best practices from other countries. This research employs a qualitative approach with a case study design. Data were collected through document analysis, interviews with educators and policymakers, and field observations in several remote areas. Thematic analysis was used to identify major patterns in educational challenges, which were then compared with education models in Japan, Vietnam, and South Korea. Data triangulation was applied to enhance the validity of findings and ensure that policy recommendations align with local needs. The study's findings indicate that low teacher welfare, a lack of professional training, and the misalignment of the curriculum with local needs are the primary factors impeding the development of education in remote areas. Japan has successfully addressed similar challenges by increasing teacher salaries and providing rigorous training programs. Vietnam has implemented education decentralization to ensure policies are more adaptive to local conditions, while South Korea has leveraged digital technology to expand education access. The implications of this research suggest that Indonesia needs to adopt a more strategic approach to improving education quality in remote areas, including investing in teacher welfare, reforming the curriculum to better suit local contexts, and strengthening technology-based educational infrastructure. This study contributes to the literature on educational disparities in developing countries and provides insights for policymakers to design more effective strategies in achieving Indonesia’s Vision 2045.